Bank Resolution and 'Bail-In' in the EU : Selected Case Studies Pre- and Post-BRRD - World Bank Group (World Bank, Vienna, 2017)
In the aftermath of the 2007/08 financial crisis, and lacking sufficient coordinated guidelines or legislation, measures to address failing financial institutions in European Union (EU) Member States were taken at national level. In an effort to improve cross border coordination as well as to reduce future dependence on public money, the European framework for managing the failure of financial institutions was reformed, building upon the financial stability Board’s key attributes. From January 1, 2015, all EU Member States were required to transpose the Bank Recovery and Resolution Directive (BRRD) into their national law. A key element of the new powers is the bail-in tool, requiring banks to recapitalize and absorb losses from within, which was made mandatory as of January 1, 2016. These case studies have been selected as examples of how some EU countries tackled the resolution of several failing European banks. The focus of the case studies is on the application of bail-in features, i.e. statutory private loss absorption outside liquidation. Most cases studies also describe other measures used to deal with distressed financial institutions, including but not limited to government guarantees, capital injections, liquidity supports, and the creation of asset management vehicles to put the bail-in into perspective. The authors hope that, nevertheless, these real life examples of European banks’ resolutions provide a useful and interesting source of reference. For more details on resolution under the BRRD, the authors invite the readers to refer to the FinSAC Guidebook Understanding Bank Recovery and Resolution in the EU: a Guidebook to the BRRD.